Concentrations of infliximab and anti-drug antibodies in relation to clinical response in patients with rheumatoid arthritis. (3rd September 2018) - Siljehult, F; Ärlestig, L; Eriksson, C; Rantapää-Dahlqvist, S
Abstract : Objective : The efficacy of anti-tumour necrosis factor-α (anti-TNF-α) treatment with infliximab (IFX) may be reduced by the development of anti-drug antibodies (ADAs). This study evaluated drug concentration and the presence of ADAs, relative to response, in rheumatoid arthritis (RA) patients treated with IFX. Method : Ninety-four RA patients were consecutively included and assessed for disease activity at baseline, and after 14, and 30 or 52 weeks. Serum IFX concentration and ADAs were analysed using in-house enzyme-linked immunosorbent assays. ADA analysis was based on binding to TNF-α-coated plates, with the lower detection limit set at mean + 2 sd of controls. Results : At 14 and 52 weeks, 74.5% of the patients had moderate to good response. Good responders had significantly higher IFX concentrations than moderate and poor responders at 52 weeks (6.6 ± 1.4 µg/mL vs 3.6 ± 1.3 µg/mL and 2.6 ± 1.6 µg/mL, respectively). An IFX concentration ≥4.66 µg/mL at 14 weeks yielded a moderate to good response at 30/52 weeks, with 91.3% specificity and 39.3% sensitivity. Eleven patients dropped out owing to lack of efficacy and eight owing to side effects; three with IFX concentration ≤ 0.5 µg/mL were ADA positive. At an IFX concentration ≤ 0.5 µg/mL, 43.8% and 30.1% at 14 and 52 weeks, respectively, were ADA positive. None of the good responders had ADAs. Conclusion : One-quarter of patients had an IFX concentration ≤ 0.5 µg/mL but only 11.7% had ADAs. High IFX concentration was related to a good response, suggesting that the lack of response could be due to a lack of IFX, rather than to the presence of ADAs.